El uso de las Tics y su incidencia en la atención al ciudadano de la Ugel Ucayali Contamana 2023 - Ramos Cachique, Cesar Augusto (2025)
The general objective of this research was to determine the incidence between the use of ICTs and citizen service of the UGEL Ucayali 2023. The study adopted a non-experimental design, of an applied type and explanatory level. The sample consisted of 100 citizens selected through probability sampling. As a data collection technique, the survey was implemented, using a questionnaire that evaluated both variables. The results showed that 23% of respondents rated the use of ICT as very appropriate, highlighting positive aspects such as the adequate response to comments and queries through social networks. As for the level of citizen service, 29% of those surveyed rated it as regular. Finally, the linear regression analysis showed a strong positive correlation between the use of ICT and citizen service, with a correlation coefficient of 0.723. The R² of 0.522 indicates that 52.2% of the variability in care is explained by the use of ICT. A coefficient of 0.476 suggests that an increase in the use of ICT significantly improves citizen service, with a statistical significance of 0.000, confirming its relevance.